The effective use of the balanced scorecard to implement strategy - Kriek, Piérre Deon (My University, 2011)
The purpose of this study was to confirm some of the factors, which had been derived from a comprehensive literature review, which influenced the effective use of the Balanced Scorecard to implement strategy. The case study method, utilising mainly semi-structured interviews for data collection, was used to test the theory against the evidence that was gathered from the case site. The research confirmed or contradicted a range of factors that assisted or hindered the effective implementation of strategy when using the Balanced Scorecard, which had been identified through the literature review, and also gave some valuable insights into some additional factors that may impact on the effectiveness of the Balanced Scorecard as a tool for strategy implementation
MBA - WBS
Keywords: Strategic planning; Balanced scorecard